Pathogenese des kolitisassoziierten Karzinoms - Vieth, Michael; Neumann, Helmut (Pathologe, 2012)
It is sometimes difficult but finally possible to distinguish colitis-associated neoplasms from sporadic neoplasms. The frequency of detection of precursor lesions of carcinoma (e.g. dysplasia, intraepithelial neoplasia and adenoma) has increased in recent years, which is most probably due to better endoscopic detection and thus improved histological diagnosis. Carcinogenesis of colitis-associated neoplasms is different from carcinogenesis in sporadic neoplasms because mutations and epigenetic changes are different or may occur at a different point in time. In the present article, these differences will be described and placed in context with carcinogenesis in ulcerative colitis.
CRIS-Team Scopus Importer:2025-03-05